Potensi Senyawa Kuersetin sebagai Antikanker Payudara melalui Pendekatan Molecular Docking - Amin, Saeful; Wihdatunnisa, Imelda; Aisyah, Rohmah; Kurniawan, Yoga Sugama (Penerbit Goodwood, 2024)
Purpose: This study aims to evaluate the potential of quercetin as an anti-breast cancer agent through a molecular docking-based literature review. Quercetin, a natural flavonoid found in various fruits and vegetables, has attracted interest due to its antioxidant, anti-inflammatory, and anticancer properties. This study focuses on its potential interaction with key molecular targets associated with breast cancer progression.. Methodology: A systematic literature review was conducted using peer-reviewed articles published between 2015 and 2024, sourced from major scientific databases such as PubMed, Scopus, and ScienceDirect. The review focused on molecular docking studies that assessed quercetin's interaction with three principal breast cancer target proteins: Human Epidermal Growth Factor Receptor 2 (HER-2), 2W3L (a mutant form of the Estrogen Receptor), and Sirtuin 1. Results: Quercetin demonstrated strong binding affinities, with docking scores ranging from -8.0 to -9.5 kcal/mol for HER-2 and 2W3L, indicating stable and favorable interactions. These interactions suggest that quercetin may interfere with breast cancer cell signaling pathways. Conclusion: The findings suggest that quercetin holds significant promise as an anti-breast cancer compound, particularly through its stable interaction with HER-2 and 2W3L. Nonetheless, further in vitro and in vivo studies are essential to validate these in silico findings and evaluate its pharmacokinetic and pharmacodynamic properties.. Limitations: This study is limited to computational data without experimental validation. Contribution: This review supports the potential of quercetin in breast cancer drug discovery and highlights the importance of structure-based drug design in identifying novel therapeutic agents.